Evaluation of sealed storage silos for grain fumigation - Cook, Samuel A.L. (Kansas State University, 2016)
Fumigation of stored grain is a common way to kill stored-grain insect pests. However, fumigating in unsealed structures is the leading cause of control failures and subsequent development of insect resistance. Sealing the storage structure is the only practical way to ensure a complete kill of all insects at all life stages. The cost, effort, and feasibility of sealing a U.S. corrugated steel silo during construction was evaluated and compared against an Australian sealed silo designed for fumigation. Gas monitoring and thermosiphon recirculation equipment was installed on both silos. Fumigation efficacy was evaluated using pressure half-life decay times, fumigant concentrations, insect bioassays, and grain quality data. Three fumigations with phosphine (PH₃) pellets or tablets and two with VAPORPH₃OS® cylinderized PH₃ and ProFume® cylinderized sulfuryl fluoride (SF) were performed in each silo for a total of ten experimental treatments. The Australian silo required 266 man-hours to construct and cost $180 for additional sealing, compared to 359 man-hours and $3,284 for constructing and sealing the U.S. silo. The Australian silo had a maximum pressure half-life decay time of 163 s versus 50 s for the U.S. silo. At application rates of 1.5 g/mᶟ of PH₃ both silos maintained an average concentration of approximately 0.28 g/mᶟ for 14 days. With thermosiphon recirculation the average minimum-to-maximum PH₃ concentration ratio in the U.S. silo was 0.52, compared to a ratio of 0.17 when fumigating without thermosiphon recirculation. Greater than 99% adult mortality was observed in all insect bioassays which included PH₃ resistant strains of R. dominica and T. castaneum. The average emergence from fumigated bioassays was 7 adult insects, compared to an average of 383 adults for the non-fumigated controls. Grain stored for 10 months in the sealed silos increased from approximately 11.5% to 17% m.c. in the top 0.3 m of grain, and decreased in test weight from approximately 77 to 65 kg/hL. Although the Australian silo retained higher fumigant concentrations than the U.S. silo, fumigations were successful in both. Long-term storage in sealed silos is a concern because grain quality can deteriorate due to condensation and mold in the top grain layer.
Keywords: Fumigation; Sealed Storage; Agriculture engineering; Grain storage; Phosphine resistance; Thermosiphon recirculation